Inhibitory Effects of Eleutherococcus senticosus Extracts on Amyloid β(25-35)-Induced Neuritic Atrophy and Synaptic Loss - Chihiro Tohda; Mahoko Ichimura; Yanjing Bai; Ken Tanaka; Shu Zhu; Katsuko Komatsu (Elsevier, 2008)
Neurons with atrophic neurites may remain alive and therefore may have the potential to regenerate even when neuronal death has occurred in some parts of the brain. This study aimed to explore effects of drugs that can facilitate the regeneration of neurites and the reconstruction of synapses even in severely damaged neurons. We investigated the effects of Eleutherococcus senticosus extracts on the regeneration of neurites and the reconstruction of synapses in rat cultured cortical neurons damaged by amyloid β (Aβ)(25-35). Treatment with Aβ(25-35) (10 μM) induced axonal and dendritic atrophies and synaptic loss in cortical neurons. Subsequent treatment with the methanol extract and the water extract of E. senticosus (10-1000 ng/ml) resulted in significant axonal and dendritic regenerations and reconstruction of neuronal synapses. Co-application of the extract and Aβ(25-35) attenuated Aβ(25-35)-induced neuronal death. We investigated neurite outgrowth activities of eleutherosides B and E and isoflaxidin, which are known as major compounds in E. senticosus. Although eleutheroside B protected against Aβ(25-35)-induced dendritic and axonal atrophies, the activities of eleutheroside E and isofraxidin were less than that of eleutheroside B. Although the contents of these three compounds in the water extract were less than in the methanol extract, restoring activities against neuronal damages were not different between the two extracts. In conclusion, extracts of E. senticosus protect against neuritic atrophy and cell death under Aβ treatment, and one of active constituents may be eleutheroside B. Keywords:: axon, dendrite, synapse, neuronal death, Eleutherococcus senticosus